A method for preparing an additive for a secondary battery electrolyte
Patent Information
- Application Number
- CN202610760401.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-05-29
- Publication Date
- 2026-08-18
AI Technical Summary
但是该路线在制备过程中会生成杂质,如氯代杂质,水解杂质等,导致产品的纯度下降
(1)本技术路线通过大量研究,首次提出并实现了将磺酰胺用于硫酸酯的制备,采用了便宜易得的试剂,避免了现有技术的贵金属催化剂和氧化剂的使用,降低了成本,减少了危险试剂氯化亚砜的使用;进行一步反应即可得到产品,该反应的收率高,成本低,具有极强的市场竞争力。
Smart Images

Figure CN122586849A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of secondary battery materials technology, and specifically relates to a method for preparing an additive for secondary battery electrolyte. Background Technology
[0002] Cyclic sulfate compounds, with their unique chemical structure and excellent performance, have become important additives in the field of lithium battery electrolytes. Compounds such as ethylene sulfate are among the most widely used. The central sulfur atom in these compounds has strong electronegativity, exhibiting superior reducing properties at the graphite anode interface compared to carbonate additives. This allows them to preferentially form a stable solid electrolyte interphase (SEI) film on the electrode surface. This film not only suppresses initial capacity loss and improves charge / discharge efficiency but also reduces electrolyte decomposition, alleviates battery expansion at high temperatures, effectively extends battery cycle life, and enhances safety performance.
[0003] The stringent performance and safety requirements of secondary batteries make the purity of cyclic sulfate compounds a critical indicator. Insufficient product purity not only degrades the stability of the SEI film and exacerbates electrode material corrosion, but can also trigger side reactions that generate gases, leading to battery swelling, increased internal resistance, and severely impacting cycle life and safety. For example, in lithium-ion batteries, low-purity cyclic sulfates may introduce byproducts such as organic impurities, metallic impurities, chloride ions, moisture, and H₂O. + Impurities such as these significantly reduce the stability of the electrolyte and shorten the battery's lifespan. Therefore, high-purity cyclic sulfate compounds are essential for ensuring the long-term stable operation of secondary batteries and fully realizing their performance advantages.
[0004] Currently reported methods for preparing sulfate esters involve reacting polyols and thionyl chloride as raw materials, followed by oxidation to obtain cyclic sulfate esters. This is one of the main methods for synthesizing sulfate esters. Current oxidation reactions mostly employ a catalyst + oxidant approach.
[0005] Chinese patents CN 118184644 A and CN 118598869 A disclose a common method for preparing sulfate ester compounds. This method involves first reacting a polyol with thionyl chloride to prepare a sulfite ester compound, then using a noble metal catalyst such as ruthenium trichloride and an oxidizing agent to oxidize the sulfite ester to a sulfate ester, yielding the target product. This preparation method uses thionyl chloride and a noble metal catalyst, introducing impurities such as chloride ions, sulfite ions, and heavy metals into the reaction system, which significantly affect lithium-ion batteries. Furthermore, the post-processing is cumbersome, resulting in low yield, poor quality, and insufficient purity. The presence of impurities and ions significantly impacts the battery's lifespan.
[0006] The conventional methods for preparing sulfate ester compounds are as follows: The intermediate vinyl polysulfite is obtained by esterification of polyol, dimethyl carbonate, and thionyl chloride. This intermediate is then oxidized in the presence of a catalyst (such as ruthenium salts or molecular sieves capable of catalyzing oxidation reactions) using an oxidizing agent (such as hydrogen peroxide, sodium periodate, sodium hypochlorite, or calcium hypochlorite). However, this route generates impurities during preparation, such as chlorinated impurities and hydrolyzed impurities, leading to a decrease in product purity.
[0007] Sulfate compounds prepared by existing technologies often contain impurities such as chloride ions, metal impurities, and sulfate ions, as well as high water content, which can easily lead to the degradation of the compounds and the generation of H+. + Sulfate ions contribute to the poor stability of sulfate ester compounds, resulting in short shelf life, stringent storage requirements, and necessitate cold chain transportation, leading to high transportation costs. Furthermore, when used as an additive in battery electrolytes, the generation of impurities can affect the performance and lifespan of lithium-ion batteries, and in more serious cases, can cause battery decomposition and combustion, posing a danger.
[0008] It is necessary to develop a novel method for preparing sulfate ester-based battery additives to obtain high-purity sulfate ester compounds, enabling stable storage of the product and ultimately extending the lifespan of lithium batteries. Summary of the Invention
[0009] To address the problems existing in the prior art, the purpose of this invention is to provide a method for preparing a secondary battery electrolyte additive. The prepared ester compound has high purity, low cost, and low content of impurities such as organic impurities, metal impurities, chloride ions, and sulfate ions. The product has high stability and long shelf life, which can greatly reduce transportation and storage costs. Moreover, when used as a battery electrolyte additive, it can enhance the stability of battery products, extend battery life, and ensure battery safety.
[0010] This invention provides a method for preparing a secondary battery electrolyte additive, comprising the following steps: mixing and reacting a compound of formula II, a compound of formula III (sulfonamide), a solvent, and a catalyst at a controlled temperature; after the reaction is complete, performing post-treatment to obtain a compound of formula I, i.e., the secondary battery electrolyte additive; the reaction equation is: Where: R1 and R2 are hydrogen atoms or Groups, and R1 and R2 are not both hydrogen atoms; R3 and R4 are hydrogen atoms or The groups are not simultaneously hydrogen atoms, and R3 and R4 are not both hydrogen atoms.
[0011] Preferably, the compound corresponding to Formula II has the structure of either Formula a or Formula b: .
[0012] This invention produces lithium-ion battery additives such as ethylene disulfate and ethylene trisulfate, which have extremely high application value.
[0013] Through extensive experimentation, this invention has discovered that by using the reagent sulfonamide under specific conditions, a one-step reaction can be achieved to cyclize with diols, thereby preparing sulfate ester compounds such as ethylene disulfate and ethylene trisulfate. This method is low in cost and produces products with high purity.
[0014] Preferably, the molar ratio of compound II to compound III is 1:2 to 5, more preferably 1:2.2 to 4.5.
[0015] Preferably, the catalyst is copper acetate, copper chloride, copper bromide or copper iodide, with copper acetate being the most preferred.
[0016] Preferably, the molar ratio of the compound of formula II to the catalyst is 1:0.1~0.8, more preferably 1:0.1~0.3.
[0017] Preferably, the solvent is acetic acid.
[0018] Preferably, the mass ratio of the compound of formula II to the solvent is 1:4 to 12, more preferably 1:4 to 6.
[0019] Currently, it has been reported that diols can undergo cyclization reactions with carbamates (urea) to produce ethylene carbonate, while reactions between sulfonamides and diols are rarely reported. This is mainly because the stability of the SN bond in sulfonamides is much greater than the CN bond stability in carbamates, making it impossible to achieve SN bond breaking and SO bond construction under conventional conditions. This invention, through extensive experimentation, creatively realizes this type of reaction, and for the first time proposes and implements the use of sulfonamides in the preparation of sulfate esters, such as the preparation of lithium-ion additives ethylene trisulfate and ethylene disulfate. It uses inexpensive and readily available reagents, avoiding the use of precious metal catalysts and oxidants in existing technologies, reducing hazardous reactions, lowering production costs, reducing impurity formation, and improving product purity.
[0020] Through extensive experimentation, this invention discovered that using acetic acid as a solvent and copper acetate, copper chloride, copper bromide, or copper iodide as catalysts, the SN bond of sulfonamides can be broken under the catalysis of copper ions. The resulting acid ester compounds exhibit high purity and low levels of organic impurities, metallic impurities, chloride ions, sulfate ions, etc., resulting in products with high stability and long shelf life. The hypothesized principle is that divalent copper ions coordinate with the O atomium of the diol, then chelate with the S atomium, thereby lowering the SN bond energy and promoting its breakage, releasing ammonia gas. The reaction mechanism is as follows: .
[0021] Copper acetate is preferred as the catalyst. Using the copper acetate + acetic acid system, the generated ammonia gas forms a salt with acetic acid, which promotes the forward reaction and produces high-purity sulfate ester compounds with high purity and low content of impurities such as organic impurities, metal impurities, chloride ions, and sulfate ions.
[0022] Preferably, the heat preservation reaction temperature is 50~100℃, more preferably 60~70℃; the heat preservation reaction time is 6~10 hours.
[0023] Preferably, the post-processing is as follows: after concentrating the reaction solution until solid precipitates, add purified water to disperse it, filter to obtain the solid, add acetonitrile to dissolve it, decolorize it with activated carbon, add purified water dropwise to the filtrate, stir for 1-2 h, filter and dry to obtain the sulfate ester compound product of formula I.
[0024] Compared with the prior art, the present invention has the following advantages: (1) Through extensive research, this technical route has for the first time proposed and realized the use of sulfonamides in the preparation of sulfate esters. It uses inexpensive and readily available reagents, avoids the use of precious metal catalysts and oxidants in existing technologies, reduces costs, and reduces the use of dangerous reagent thionyl chloride. The product can be obtained in one step. The reaction has a high yield and low cost, and has strong market competitiveness.
[0025] (2) The sulfate ester compounds prepared by the present invention have high purity, low cost, low content of impurities such as organic impurities, metal impurities, chloride ions, and sulfate ions, high product stability, long shelf life, and can greatly reduce transportation and storage costs. When used as an additive for battery electrolyte, it can enhance the stability of battery products, give batteries a longer service life, and ensure the safety of battery products. Attached Figure Description
[0026] Figure 1 : HNMR spectrum of ethylene disulfate prepared in Example 1; Figure 2 HPLC chromatogram of vinyl disulfate prepared in Example 1; Figure 3 : HNMR spectrum of ethylene trisulfate prepared in Example 2; Figure 4 HPLC chromatogram of ethylene trisulfate prepared in Example 2. Detailed Implementation
[0027] The present invention will be further illustrated below with specific embodiments. These embodiments are merely illustrative and do not limit the scope of the invention.
[0028] Example 1:
[0029] A method for preparing ethylene disulfate, an additive for secondary battery electrolytes, includes the following steps: (1) 122g (1.0mol) of compound a, 288g (3.0mol) of compound III (sulfonamide), 610g of acetic acid as solvent, and 24.4g (0.13mol) of copper acetate as catalyst were kept at 65°C for 6 hours. After the reaction was completed under central control, the mixture was concentrated under reduced pressure until the residue was solid. Then, 732g of water was added, and the solid was dispersed by stirring. The mixture was filtered, and the filter cake was not dried before proceeding to step (2). (2) Add 366g of acetonitrile, stir to dissolve, add 3g of activated carbon for decolorization for 1 hour, filter, add 1098g of purified water dropwise to the filtrate while stirring, stir for 1 hour, filter, dry the filter cake, and obtain 218g of the product ethylene disulfate, with a yield of 89% and a purity of 99.99%; the HNMR spectrum is shown in the figure. Figure 1 HPLC chromatograms are shown below. Figure 2 .
[0030] .
[0031] Comparative Example 1 Comparative Example 1 is basically the same as Example 1, except that copper acetate catalyst is not added.
[0032] Result: Compound a, the raw material, did not react, and no diethylene sulfate product was obtained.
[0033] Comparative Example 2 Comparative Example 2 is basically the same as Example 1, except that copper chloride is used instead of copper acetate in an equimolar ratio as the catalyst.
[0034] Results: Vinyl disulfate was prepared with a purity of 98.6% and a yield of 73%.
[0035] Comparative Example 3 Comparative Example 3 is basically the same as Example 1, except that: the catalyst uses ferric acetate in an equimolar ratio instead of copper acetate.
[0036] Results: Vinyl disulfate was prepared with a purity of 86.2% and a yield of 23%.
[0037] Comparative Example 4 Comparative Example 4 is basically the same as Example 1, except that: the catalyst uses palladium acetate in an equimolar ratio instead of copper acetate.
[0038] Results: Vinyl disulfate was prepared with a purity of 68.5% and a yield of 10%.
[0039] Comparative Example 5 This comparative example uses a conventional process: 122 g (1.0 mol, 1.0 eq) of erythritol was added to 610 g of dimethyl carbonate solvent, followed by 261.7 g (2.2 mol, 2.2 eq) of thionyl chloride. The mixture was heated to 30-40 °C to induce esterification. After the reaction was complete, the mixture was concentrated to dryness to obtain the intermediate product, vinyl disulfite. 610 g of acetonitrile was then added, and the mixture was stirred until dissolved. Ruthenium trichloride hydrate (0.61 g, 0.5%) was added as a catalyst, and the intermediate product was oxidized using sodium periodate as an oxidant. After post-treatment, crude vinyl disulfite was obtained. The crude product was then dissolved in 20 times its volume of acetonitrile. After decolorization and adsorption of metal impurities by stirring with activated carbon and mercaptosilica, the mixture was filtered, cooled to below 20 °C, and allowed to crystallize for 1.5 h. The crystals were then filtered, dried under vacuum, and the vinyl disulfite product was obtained with a liquid phase purity of 99.80% and a yield of 78%.
[0040] The reaction equation is shown below: .
[0041] Comparative Example 6 Comparative Example 6 is basically the same as Example 1, except that N,N-dimethylformamide is used instead of acetic acid as the solvent.
[0042] Results: Vinyl disulfate was prepared with a purity of 81.2% and a yield of 68%.
[0043] I. Comparison of quality standards and shelf life of disulfates: The vinyl disulfate products prepared in Example 1 and Comparative Example 5 were tested, and the test results are shown in Table 1: Accelerated stability testing of decomposition rate after 6 months of storage: The vinyl disulfate products prepared in Example 1 and Comparative Example 5 were packaged using conventional packaging methods, as follows: inner layer of high-density polyethylene drum; outer layer of aluminum foil bag, vacuum packaging. After packaging, accelerated stability tests were conducted (temperature 40℃±2℃, humidity 75%RH±5%RH, time 6 months), and the results are shown in the table below.
[0044] Table 1 Note: The implementation standard is an internal corporate standard.
[0045] Example 2
[0046] A method for preparing ethylene trisulfate, an additive for secondary battery electrolytes, includes the following steps: (1) 182g (1.0mol) of compound b, 384g (4.0mol) of compound III (sulfonamide), 910g of acetic acid, and 24.4g (0.13mol) of copper acetate were placed at 60°C and kept at that temperature for 7 hours. After the reaction was completed under controlled temperature, the mixture was concentrated under reduced pressure until the residue was solid. Then, 1092g of water was added and the solid was dispersed by stirring. The mixture was filtered and the filter cake was not dried before proceeding to step (2). (2) Add 546g of acetonitrile, stir to dissolve, add 3g of activated carbon for decolorization for 1 hour, filter, add 1638g of purified water dropwise to the filtrate while stirring, stir for 1 hour, filter, dry the filter cake, and obtain 320g of the product ethylene disulfate, with a yield of 87% and a purity of 99.99%. The HNMR spectrum is shown in [reference needed]. Figure 3 HPLC chromatograms are shown below. Figure 4 .
[0047] Comparative Example 7 This comparative example uses a conventional process: (1) 182.0 g (1.0 mol, 1.0 eq) of D-mannitol, 910 g of dimethyl carbonate and 496.0 g (4.0 mol, 4.0 eq) of thionyl chloride were mixed and subjected to esterification reaction at 60 °C. After 5 hours of reaction, the mixture was concentrated to dryness to obtain the intermediate product vinyl trisulfite. 0.5% mol of ruthenium trichloride catalyst was added, and then 3.1 mol of sodium periodate oxidant was added to oxidize the intermediate product to obtain crude vinyl trisulfite (TriDTD); 290.7 g, yield 79.0%; (2) The crude ethylene trisulfate was dissolved by stirring with 10 times the volume of solvent acetonitrile. Then, it was decolorized and metal impurities were adsorbed by 0.5% activated carbon and 1% mercaptosilica. Purified water was added dropwise over 2 hours. After the addition was completed, the mixture was kept warm for 1 hour, filtered, and dried to obtain crystal form B with a weight of 247.1 g, a yield of 85%, and a purity of 95.39%.
[0048] The reaction equation is as follows: .
[0049] During the preparation process, the hydroxyl groups of mannitol are replaced by Cl, generating chlorinated impurities. The presence of these impurities affects the purity of the product and makes it difficult to purify. The purity is below 99%. The residual impurities not only damage the stability of the SEI film and aggravate the corrosion of the electrode material, but may also trigger side reactions to generate gas, causing the battery to swell and the internal resistance to increase. This seriously affects the cycle life and safety of use, making it impossible to use as a battery additive in secondary battery electrolytes.
[0050] Comparison of quality standards and shelf life of ethylene trisulfate: The vinyl trisulfate products prepared in Example 2 and Comparative Example 7 were tested, and the test results are shown in Table 2: Accelerated stability testing for decomposition rate after 6 months of storage: The ethylene trisulfate products prepared in Example 2 and Comparative Example 7 were packaged using conventional packaging methods, as follows: inner layer of high-density polyethylene drum; outer layer of aluminum foil bag, vacuum packaging. After packaging, accelerated stability tests were conducted (temperature 40℃±2℃, humidity 75%RH±5%RH, time 6 months), and the results are shown in the table below.
[0051] Table 2 Note: The implementation standard is an internal corporate standard.
[0052] In summary, due to the stringent performance and safety requirements of secondary batteries, the purity of cyclic sulfate ester compound additives becomes a critical indicator. Insufficient product purity not only disrupts the formation and stability of the SEI film and exacerbates electrode material corrosion, but may also trigger side reactions that generate gas, leading to battery swelling, increased internal resistance, and severely impacting the cycle life and safety of the secondary battery. The ethylene disulfate and ethylene trisulfate products prepared in this invention both achieve a purity of over 99.9%. High-purity sulfate ester additives can be successfully applied to secondary battery electrolytes, providing a crucial foundation for ensuring long-term stable operation and fully leveraging the performance advantages of secondary batteries.
[0053] Furthermore, this invention is the first to propose and realize the use of sulfonamides in the preparation of sulfate esters, producing triethylene sulfate and diethylene sulfate with a purity of 99.9%. The process of this invention involves only one reaction step, which is less than conventional processes. It also avoids the use of highly corrosive thionyl chloride and expensive precious metal ruthenium catalysts, as well as dangerous oxidation reactions, reducing the content of metal element impurities and other organic impurities, thus meeting the stringent requirements of additives for the performance and safety of secondary batteries.
[0054] The present invention achieves the best reaction effect when copper acetate is selected as the catalyst and acetic acid is selected as the solvent, with both the yield and purity being higher than those of products prepared by conventional processes.
[0055] III. Secondary Battery Performance Testing Since batteries spend most of their time in standby mode, changes in their state during storage are a crucial indicator of their marketability. To expedite the experiment, high-temperature storage was chosen to accelerate the reaction, simulating the self-discharge effects and aging processes that batteries undergo during routine storage.
[0056] Preparation of positive electrode: The preparation method of the positive electrode sheet is as follows: Lithium cobalt oxide (LiCoO2), polyvinylidene fluoride (PVDF), and conductive additive (Super P) are mixed in a mass ratio of 96:2:2. N-methylpyrrolidone (NMP) is added as a solvent and stirred in a vacuum mixer until a uniform and fluid positive electrode active slurry is formed. The slurry is then uniformly coated on both surfaces of an aluminum foil. The coated aluminum foil is then dried, rolled, and slit to finally obtain the desired positive electrode sheet.
[0057] Preparation of negative electrode: The negative electrode sheet is prepared as follows: Artificial graphite, silicon suboxide, sodium carboxymethyl cellulose, styrene-butadiene rubber, and conductive carbon black are mixed in a mass ratio of 79.5:15:2.5:1.5:1.5. Deionized water is added, and the mixture is stirred under vacuum to form a homogeneous slurry. The slurry is then uniformly coated onto both sides of a copper foil, first dried at room temperature, then thoroughly dried at 80°C. Finally, the negative electrode sheet is obtained through cold pressing and slitting.
[0058] Preparation of electrolyte for blank control group: The electrolyte is prepared as follows: Ethylene carbonate, propylene carbonate, diethyl carbonate, and propyl propionate are mixed in a mass ratio of 10:20:40:30 as an organic solvent, and then 1 mol / L lithium hexafluorophosphate is added to form a lithium salt base system. Next, 5% fluoroethylene carbonate and 2% hexanetrionitrile (by mass of the total electrolyte) are introduced into the system as functional additives. After all components are thoroughly stirred and dissolved, and the moisture and free acid levels are tested and found to be within acceptable limits, the target electrolyte is obtained.
[0059] Preparation of electrolyte group A: Add 1% by mass of vinyl disulfate prepared in Example 1 to the electrolyte group blank; Preparation of electrolyte for group B: Add 1% by mass of ethylene disulfate prepared in Comparative Example 5 to the electrolyte of the blank group. Preparation of electrolyte for group C: Add 1% by mass of ethylene trisulfate prepared in Example 2 to the electrolyte of the blank group; Preparation of electrolyte for group D: Add 1% by mass of ethylene trisulfate prepared in Comparative Example 7 to the electrolyte of the blank group. Preparation of secondary batteries: The battery is manufactured as follows: First, the positive electrode, separator and negative electrode are stacked and wound into a cell in sequence; then the cell is placed in the outer packaging aluminum foil, each group of electrolytes is injected, and then vacuum sealing, standing, formation, shaping and sorting are carried out to finally obtain a battery with a working voltage range of 2.8V-4.25V.
[0060] After the battery is filled with electrolyte, it is activated using standard methods. After full activation, the battery is stored at 60°C for 7 days, and then its capacity retention is tested.
[0061] Test section: (1) Room temperature cycling performance test At 25°C, the secondary battery is charged at a constant current of 1C to 4.25V, then charged at a constant voltage of 4.25V to a cutoff current of 0.05C, left to rest for 10 minutes, and then discharged at a constant current of 1C to 2.8V, left to rest for 5 minutes. This constitutes one charge-discharge cycle. The discharge capacity at this point is recorded as C0. This charge-discharge cycle process is repeated for the same secondary battery, and the discharge capacity C1 of the 300th cycle is recorded. The cycle capacity retention rate of the battery is P300 = C1 / C0 × 100%.
[0062] (2) High-temperature storage performance test At 25°C, the secondary battery is charged at a constant current of 1C to 4.25V, then charged at a constant voltage of 4.25V to the cutoff current of 0.05C, left to stand for 10 minutes, and then discharged at a constant current of 1C to 2.8V, left to stand for 5 minutes. This constitutes one charge-discharge cycle. Record the discharge capacity D0 at this point.
[0063] The secondary battery was stored at 60°C for 60 days. Afterward, the secondary battery was removed and cooled to a surface temperature of 25°C.
[0064] Subsequently, at 25°C, it was discharged at a constant current of 1C to 2.8V, then charged at a constant current of 1C to 4.25V, and then charged at a constant voltage of 4.25V to the cutoff current of 0.05C. After resting for 10 minutes, it was discharged at a constant current of 1C to the termination voltage of 2.8V to obtain the discharge capacity D1 after high-temperature storage.
[0065] High-temperature storage capacity retention rate (%) = (D1 / D0) × 100%.
[0066] (3) Power performance test The power performance of a secondary battery is characterized by its direct current resistance (DCR). Generally, the lower the DCR, the better the battery's power performance.
[0067] At 25°C, the secondary battery was charged at a constant current of 1C to 4.25V, then charged at a constant voltage of 4.25V to a cutoff current of 0.05C, allowed to stand for 30 minutes, and then discharged at a constant current of 1C for 0.5 hours, allowed to stand for 30 minutes, and the voltage V1 after standing was recorded. Subsequently, it was discharged at 4C for 30 seconds, and the voltage V2 at the end of the discharge was recorded.
[0068] The battery's DCR = (V1 - V2) / I, where I = the current corresponding to a 4C rate.
[0069] The test results are detailed in the table below: Table 3 As shown in the table above, the secondary batteries with additives from groups A, B, C, and D exhibit higher cycle capacity retention and high-temperature storage capacity retention, as well as lower internal resistance, compared to the control group. However, the secondary batteries with added ethylene disulfate (group A) show significant advantages over those with added ethylene disulfate (group B) prepared using conventional processes in terms of cycle capacity retention, high-temperature storage capacity retention, and reduced internal resistance. Similarly, the secondary batteries with added ethylene trisulfate (group C) also show significant advantages over those with added ethylene trisulfate (group D) prepared using conventional processes in terms of cycle capacity retention, high-temperature storage capacity retention, and reduced internal resistance.
[0070] It should be noted that this application is not limited to the above-described embodiments. The above embodiments are merely examples, and any embodiments with the same structure and effect as the technical concept within the scope of this application are included in the technical scope of this application. Furthermore, various modifications that can be conceived by those skilled in the art to the embodiments, and other ways of constructing by combining some of the constituent elements of the embodiments, without departing from the spirit of this application, are also included in the scope of this application.
Claims
1. A method for preparing an additive for a secondary battery electrolyte, characterized by: Includes the following steps: Compounds of Formula II and III (sulfonamide), solvent, and catalyst are mixed and reacted at a controlled temperature. After the reaction is complete, post-treatment is performed to obtain compound I, which is the secondary battery electrolyte additive. The reaction equation is as follows: ; wherein: R1, R2are hydrogen atoms or a group, and R1and R2are not simultaneously hydrogen atoms; R3 and R4 are hydrogen atoms or The groups are not simultaneously hydrogen atoms, and R3 and R4 are not both hydrogen atoms.
2. The preparation method according to claim 1, characterized in that: The molar ratio of compound II to compound III is 1:2~5.
3. The preparation method according to claim 1, characterized in that: The catalyst is copper acetate, copper chloride, copper bromide, or copper iodide.
4. The preparation method according to claim 3, characterized in that: The catalyst is copper acetate.
5. The preparation method according to claim 3, characterized in that: The molar ratio of compound II to catalyst is 1:0.1~0.
8.
6. The preparation method according to claim 1, characterized in that: The solvent is acetic acid.
7. The preparation method according to claim 6, characterized in that: The mass ratio of compound II to solvent is 1:4~12.
8. The preparation method according to claim 1, characterized in that: The molar ratio of compound II to catalyst is 1:0.1~0.3; the mass ratio of compound II to solvent is 1:4~6.
9. The preparation method according to claim 1, characterized in that: The heat preservation reaction temperature is 50~100℃; the heat preservation reaction time is 6~10 hours.
10. The preparation method according to claim 1, characterized in that: The post-processing is as follows: after concentrating the reaction solution until solid precipitates, add purified water to disperse it, filter to obtain solid, add acetonitrile to dissolve it, decolorize it with activated carbon, add purified water dropwise to the filtrate, stir for 1-2 h, filter and dry to obtain the compound product of formula I.
Citation Information
Patent Citations
Polyol carbonate bisulfate compound and preparation method thereof
CN118184644A
Synthesis method and application of sulfate compound
CN118598869A